The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1371/journal.pone.0019091
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Effect of Copy Number Variations on the Risk of Type 2 Diabetes in a Korean Population

Abstract: BackgroundUnlike Caucasian populations, genetic factors contributing to the risk of type 2 diabetes mellitus (T2DM) are not well studied in Asian populations. In light of this, and the fact that copy number variation (CNV) is emerging as a new way to understand human genomic variation, the objective of this study was to identify type 2 diabetes–associated CNV in a Korean cohort.Methodology/Principal FindingsUsing the Illumina HumanHap300 BeadChip (317,503 markers), genome-wide genotyping was performed to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
1
12
1
Order By: Relevance
“…Bae et al found three new regions with CNVs (chr15: 45994758–45999227, chr22: 20722473–21702142, and chr18: 3559620–3561217) that were significantly associated with the risk of T2D, particularly, the 15q21.1 region of chr15: 45994758–45999227 [9]. We found a significant association between the gain in the copy number in intergenic regions with abdominal obesity and increasing BMI.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Bae et al found three new regions with CNVs (chr15: 45994758–45999227, chr22: 20722473–21702142, and chr18: 3559620–3561217) that were significantly associated with the risk of T2D, particularly, the 15q21.1 region of chr15: 45994758–45999227 [9]. We found a significant association between the gain in the copy number in intergenic regions with abdominal obesity and increasing BMI.…”
Section: Discussionsupporting
confidence: 55%
“…At least two distinct pathways are known to be involved in the formation of CNVs-associated diseases: unequal meiotic recombination and replication errors. In particular, CNVs associated with diseases of polygenic origin such as autism [7], metabolic syndrome, obesity [8], and type 2 diabetes (T2D) [9] have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…We further merged these data with genome-wide SNP data for 50 randomly sampled Korean individuals from Seoul who were originally used as a control group in a genome-wide association study. 13 With the inclusion of the Korean data, the number of overlapping SNPs was reduced to 65 256. The list of populations used in this study is shown in Table 1.…”
Section: Sample Datamentioning
confidence: 99%
“…Each locus had previously been identified in SNP-based studies. Another GWAS of CNVs, however, failed to observe robust associations between CNVs and the risk of T2D in a Korean population [99]. These analyses suggest that common CNVs on existing platforms are not likely to have major contributions to T2D genetic susceptibility.…”
Section: Copy Number Variantsmentioning
confidence: 98%
“…However, to date there are few reported associations between common CNVs and obesity and T2D [9799]. In 2010, the Well come Trust Case Control Consortium performed a GWAS between CNVs and eight common human diseases in European populations, confirming three loci where CNVs were associated with Crohn’s disease ( IRGM locus ), rheumatoid arthritis and type 1 diabetes (HLA loci), and T2D ( TSPAN8 locus ) [98].…”
Section: Copy Number Variantsmentioning
confidence: 99%